Regulatory Barriers to Climate Action: Evidence from Conservation Areas in England - Thiemo Fetzer (Center for Economic Studies and ifo Institute (CESifo), 2023)
Preserving heritage is an important part of maintaining collective identity for future generations. Yet, culturally defined notions of "heritage" or "character", in the context of the climate crisis, may be a barrier to individual and collective climate action to tackle a much more existential threat to those future generations. Studying data for more than half of the English housing stock, I show that conservation area status – a rather fluffy area-based designation that intends to protect the unique character of a neighborhood – not to be confused with preservation of historic buildings – in England may be responsible for up to 3.2 million tons of avoidable CO2 emissions annually. Using a suite of micro-econometric methods and alternative identification strategies ranging from saturated specifications, border discontinuity, matching estimation and an instrumental variables approach leveraging World War II wartime destruction in London – I show that properties in conservation areas have a notable worse energy efficiency; experience lower investment in retrofitting and consume notably higher levels of energy owing to poor energy efficiency. Effect sizes are very consistent comparing engineering based energy consumption estimates with actual consumption data. Effects can be directly attributed to planning requirements for otherwise permitted development that only apply to properties by virtue of them being located inside a conservation area.
Keywords: Q54; Q55; R14; R48; N74; 330; climate crisis; collective action; zoning; climate adaptation